ANALYSIS OF TOURISM POTENTIAL AT KUTA JUNGAK VILLAGE, PAKPAK BHARAT REGENCY USING 4A (ATTRACTION, ACCESSIBILITY, AMENITIES, ANCILLARY) - Deafani Clara Sinaga; Nova Bernedeta Sitorus (Jurnal Ilmiah Global Education, 2023)
The development of tourist villages is one of the programs carried out by the government to promote tourism in Indonesia, this is supported by the interest of the people who are starting to visit tourist destinations such as tourist villages because they have different natural and cultural beauties and have their own characteristics - each village. Another thing is also because the development of Tourism Villages is able to create an economic leap for the surrounding community and at the same time makes the value of tourism in Indonesia stronger. Kuta Jungak Village, which is in Pakpak Bharat Regency, is one of the tourist villages in the priority destination area in North Sumatra and needs to be considered and developed. This study aimed to identify the potential of Tourist Attraction in Kuta Jungak Village, Pakpak Bharat Regency using the 4A concept (Attraction, Accessibility, Amenities, Ancillary). Kuta Jungak Village has natural tourism potential in the form of rice fields, hills, and streams. With this potential, it can be managed and enriched so that it can be developed into a tourism potential in Kuta Jungak Village. Accessibility to the Kuta Jungak Tourism Village can be said to be not too easy. The condition of the road to Kuta Jungak Tourism Village is still not entirely good. the component of Amenities Services of Kuta Jungak Village, Pakpak Bharat Regency does not yet have adequate facilities for tourists. Provision of skills and knowledge for POKDARWIS and BUMDES has been carried out, the contribution made by the local central government, Tourism and Culture Office of Pakpak Bharat Regency, they carry out Tourism Awareness activities for POKDARWIS Kuta Jungak Tourism Village.